Respiratory patient experience of measures to reduce risk of COVID-19: findings from a descriptive cross-sectional UK wide survey. Issue 9 (9th September 2020) - Philip, Keir; Cumella, Andrew; Farrington-Douglas, Joe; Laffan, Michael; Hopkinson, Nicholas
Abstract : Objectives: To assess the experience of people with long-term respiratory conditions regarding the impact of measures to reduce risk of COVID-19. Design: Analysis of data (n=9515) from the Asthma UK and British Lung Foundation partnership COVID-19 survey collected online between 1 and 8 April 2020. Setting: Community. Participants: 9515 people with self-reported long-term respiratory conditions. 81% female, age ranges from ≤17 years to 80 years and above, from all nations of the UK. Long-term respiratory conditions reported included asthma (83%), chronic obstructive pulmonary disease (10%), bronchiectasis (4%), interstitial lung disease (2%) and 'other' (<1%) (eg, lung cancer and pulmonary endometriosis). Outcome measures: Study responses related to impacts on key elements of healthcare, as well as practical, psychological and social consequences related to the COVID-19 pandemic and social distancing measures. Results: 45% reported disruptions to care, including cancellations of appointments, investigations, pulmonary rehabilitation, treatment and monitoring. Other practical impacts such as difficulty accessing healthcare services for other issues and getting basic necessities such as food were also common. 36% did not use online prescriptions, and 54% had not accessed online inhaler technique videos. Psychosocial impacts including anxiety, loneliness and concerns about personal health and family were prevalent. 81% reported engaging in physical activity. Among the 11% who were smokers, 48% reported they were planning to quit smoking because of COVID-19. Conclusions: COVID-19 and related social distancing measures are having profound impacts on people with chronic respiratory conditions. Urgent adaptation and signposting of services is required to mitigate the negative health consequences of the COVID-19 response for this group.